OPPORTUNITIES TO OPTIMIZE ANTIEPILEPTIC THERAPY WITH USE OF PHARMACOGENETIC BIOMARKERS - T. V. Dokukina; M. V. Makhrov; I. V. Gaidukevich; A. A. Gilep; T. S. Golubeva; F. P. Khlebokazov; N. N. Misyuk; P. P. Korolevich (Эпилепсия и пароксизмальные состояния, 2016)
Pharmacogenetics allows to determine the cause of the ineffectiveness of drug therapy for certain groups of people who do not respond to treatment or exhibiting an inadequate response to a standard dose of the drug. Pharmacogenetic test can predict the speed and features of a metabolism of antiepileptic drugs in patients with epilepsy, depending on the activity involved in their metabolism enzyme systems and conveyors, that allows to individualize drug therapy in epileptological practice, to avoid side effects.